2018
DOI: 10.1029/2018gl079812
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Observations of Pulsating Aurora Associated With Chorus Element Structures: Coordinated Arase Satellite‐PWING Observations

Abstract: Rapid (<1 s) intensity modulation of pulsating auroras is caused by successive chorus elements as a response to wave‐particle interactions in the magnetosphere. Here we found that a pulsating auroral patch responds to the time spacing for successive chorus elements and possibly to chorus subpacket structures with a time scale of tens of milliseconds. These responses were identified from coordinated Arase satellite and ground (Gakona, Alaska) observations with a high‐speed auroral imager (100 Hz). The temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 47 publications
(102 reference statements)
2
39
0
Order By: Relevance
“…More recently, such a correlative behavior was captured for the first time during a similar event of ground-satellite conjunction 38 . By comparing the two cases showing clear and unclear internal modulations of PsA, we succeeded in proving that less-structured "hiss-like" chorus emission 35,36 produces PsAs without the ~3 Hz internal modulation.…”
Section: Discussionmentioning
confidence: 86%
“…More recently, such a correlative behavior was captured for the first time during a similar event of ground-satellite conjunction 38 . By comparing the two cases showing clear and unclear internal modulations of PsA, we succeeded in proving that less-structured "hiss-like" chorus emission 35,36 produces PsAs without the ~3 Hz internal modulation.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, chorus waves are one of the most important loss mechanisms of plasma sheet electrons via pitch angle scattering (e.g., Horne et al, ). The scattered electrons into the upper atmosphere could then generate microbursts (e.g., Breneman et al, ; Nakamura et al, ; Shumko et al, ), pulsating aurora (e.g., W. Li et al, ; Nishimura et al, ; Nishimura, Bortnik, Li, Thorne, Lyons, et al, ; Nishimura, Bortnik, Li, Thorne, Chen, et al, ; Ozaki et al, , ), and diffuse aurora (e.g., Ni et al, ; Thorne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At a higher L shell, that is, L ~ 11, Agapitov et al () showed a case with a larger scale size of chorus element, around 3,000 km, using Time History of Events and Macroscale Interactions during Substorms (THEMIS) observations. Moreover, the scale size of chorus waves is estimated by mapping the size of microburst and pulsating aurora onto the equatorial plane (e.g., Breneman et al, ; Nishimura, Bortnik, Li, Thorne, Lyons, et al, ; Nishimura, Bortnik, Li, Thorne, Chen, et al, ; Ozaki et al, , ; Shumko et al, ). On the nightside at L ~ 8, the latitudinal (longitudinal) size of pulsating aurora is found to be a few tens (hundreds) kilometers, which is roughly 3,000–7,000 km when mapping onto the equatorial plane (Nishimura, Bortnik, Li, Thorne, Chen, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations